1967
DOI: 10.1177/15.4.216
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Coenzyme Q on the Histochemical Succinic Tetrazolium Reductase Reaction: A Histochemical Study

Abstract: The role played by coenzyme Q (CoQ) in the succinic tetrazolium reductase reaction was investigated. Fresh cryostat sections of normal rat tissues were extracted with acetone to remove CoQ from the tissue sections and the acetone-extracted sections were reconstituted with CoQ-lecithin complexes. The incubation film method for tetrazolium reductases was used as a test system, using succinate as a substrate. Sections from which CoQ had been selectively extracted did not reduce the tetrazolium to its formazan, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1968
1968
1982
1982

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…The enzymatic tetrazolium reducing reaction was carried out at 37°C for 15 minutes after various procedures for control. On the other hand, the effects of the extraction of CoQ and lipid, and restoration with CoQ on the succinate tetrazolium reductase reaction were investigated in the specimens of the spiral organ : for the extraction of CoQ aqueous acetone dilution (96%) was used as prefixative bath according to Horwitz et al (1967) (6) and for restoration of CoQ CoQ7 (suspension in distilled water, Takeda Chemical Industries, Ltd.) was added to the acetone-extracted specimens. The incubation medium for SDH consisted of: 5 ml sodium succinate (0.2 M) in distilled water; 5.0 ml phosphate buffer (0.2 M, pH 7.6) ; 10.0 ml Nitro-BT (1 mg/ml) in distilled water.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The enzymatic tetrazolium reducing reaction was carried out at 37°C for 15 minutes after various procedures for control. On the other hand, the effects of the extraction of CoQ and lipid, and restoration with CoQ on the succinate tetrazolium reductase reaction were investigated in the specimens of the spiral organ : for the extraction of CoQ aqueous acetone dilution (96%) was used as prefixative bath according to Horwitz et al (1967) (6) and for restoration of CoQ CoQ7 (suspension in distilled water, Takeda Chemical Industries, Ltd.) was added to the acetone-extracted specimens. The incubation medium for SDH consisted of: 5 ml sodium succinate (0.2 M) in distilled water; 5.0 ml phosphate buffer (0.2 M, pH 7.6) ; 10.0 ml Nitro-BT (1 mg/ml) in distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Klingenberg and Kroger (1967) (7) reveal that the function of CoQ in the respiratory chain is to form a collecting pool for hydrogen from the various dehydrogenases. Horwitz et al (1967) (6) suggest that CoQ acts as essential electron carrier in the succinate tetrazolium reductase reaction in fresh cryostat sections of the rat organs. The present authors also confirmed the role of CoQ Fin.…”
Section: The Role Of Coq In the Electron Transfer System Or Respiratomentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondrial flavoprotein localization Tetrazolium reduction to insoluble, electron-dense, blue and purple formazans suitable for both light and electron microscope detection, by mitochondria and peroxisomes is attributable to flavoprotein enzymes (Brodie and Gots, 1952;Lester and Smith, 1961) or to flavoproteins plus a natural or artificial electron carrier corresponding to the link between flavoprotein and cytochrome b in the electron transport chain (Vitamin K, Slater, 1959;Coenzyme Q, or phenazine methyl sulfate (PMS) Horowitz et al, 1967). Only three mitochondrial flavoprotein systems are subject to tetrazolium localization:…”
Section: Tetrazolium Localization Of Flavoprotein Oxidasesmentioning
confidence: 99%